The Image of Africa in Ghana's Press The Influence of Global News Organisations - Serwornoo, Michael Yao Wodui (Global Communications, 2021)
"The Image of Africa in Ghana's Press is a comprehensive and highly analytical study of the impact of foreign news organisations on the creation of an image of Africa in its own press. Identifying a problematic focus on the Western media in previous studies of the African media image, Serwornoo uses the Ghanaian press as a case study to explore the effects of centuries of Afro-pessimistic discourse in the foreign press on the continent's self-description. This study brings together a number of theoretical approaches, including newsworthiness, intermedia agenda setting, postcolonial theory and the hierarchy of influences, to question the processes underpinning the creation of media content. It is particularly innovative in its application of the methodological frameworks of ethnographic content analysis and ethnographic interview techniques to unveil the perspectives of journalists and editors. The Image of Africa in Ghana's Press presents a vital contribution of the highest academic standard to the growing literature surrounding Afro-pessimism and postcolonial studies. It will be of great value to scientists in the field of journalism studies, as well as researchers interested in the merging of journalism research, postcolonial studies, and ethnography. "